Drug resistance pattern and clonality in H. pylori strains - Varsha Singh; Shrutkirti Mishra; Pushpa Maurya; GRKoteswar Rao; Ashok Kumar Jain; Vinod Kumar Dixit; Anil Kumar Gulati; Gopal Nath (Journal of Infection in Developing Countries)
Background: This aim of this work was to determine the in vitro activity of clarithromycin, amoxycillin, metronidazole and tetracycline against Helicobacter pylori and clonality among resistant and sensitive strains isolated from North India. Methodology: A total of 68 H. pylori isolates from peptic ulcer disease and non ulcer dyspepsia patients were examined. These strains were subjected for determination of minimum inhibitory concentration of clarithromycin, amoxycillin, metronidazole and tetracycline. For molecular characterization of resistant and sensitive strains, enterobacterial repetitive intergenic consensus sequences (ERIC) and random amplified polymorphic DNA-PCR (RAPD-PCR) methods were used. Results: All the tested isolates were found resistant to metronidazole, while 65% were resistant to amoxycillin and 4.7% were resistant to clarithromycin. However, none of the isolates were found to be resistant to tetracycline. Molecular fingerprinting and cluster analysis of resistant and sensitive strains did not give clues for clonal spread of resistant strains. Conclusions: Various chromosomal mutations were seen in the putative resistance genes of resistant strains, possibly indicating selection pressure as the major cause of high resistance.